Brain mapping in multiple sclerosis: Lessons learned about the human brain - Filippi, Massimo; Preziosa, Paolo; Rocca, Maria A. (NeuroImage (Orlando, Fla.), 2019)
The application of structural and functional magnetic resonance imaging (MRI) techniques in patients with multiple sclerosis (MS) has certainly helped to improve our understanding of the mechanisms responsible for clinical disability and cognitive impairment in this condition. The numerous studies performed in MS patients have also provided many lessons on the structure-function relationships in the human brain, which could be applied to healthy subjects and to patients affected by other neurological conditions. The findings have allowed a better understanding of the processes involved in the loss of function after central nervous system (CNS) damage, and clarified the substrates of specific symptoms (e.g., cognitive impairment and fatigue), which should aid clinical recovery and help in the monitoring of disease progression. In this review, important examples of how the application of different MRI techniques in MS might provide relevant information on the human brain are discussed. These include how damage to strategic white matter tracts can cause symptoms due to a disconnection mechanism and how involvement of a specific brain network, independent of the underlying pathological substrate, might determine certain symptoms. The role of functional and structural plasticity in clinical recovery (following an acute relapse or promoted by rehabilitation) and the mechanisms that might become the target of treatment aimed at function recovery are also considered. The ways in which network- and system-based analysis can reshape current understanding of the brain structure-function relationships are discussed. Finally, there is speculation about the relevance of inherited or acquired factors, such as age, comorbidity, brain reserve and cognitive reserve, which are likely to influence the relation between CNS damage and disease clinical manifestations. •A disconnection syndrome can determine clinical impairment in neurological diseases.•Central fatigue may arise from damage to frontal cortico-subcortical connections.•Neuroplasticity occurs in neurological diseases, mitigating brain damage effects.•MRI advances are improving our understanding of brain structure-function correlation.•Several factors influence relations between brain damage and clinical manifestations.